ترجمة حروف الجرّ في القرآن الكريم: مقارنة بين ترجمتي بيكتال ومجمع الملك فهد (Translation of Prepositions (Ḥurūf Jarr) in the Qur’an: A Comparative Analysis of the Translations of Pickthall and those by King Fahd Complex) - إبراهيم, مجدي حاج; السامرائي, إحسان علي جميل (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
الملخّص تهدف هذه الدراسة إلى تتبع عمليّة ترجمة حروف الجرّ في القرآن الكريم إلى اللغة الإنجليزيّة من أجل الوقوف على دور معنى حرف الجرّ في أداء المعنى، وما لهذا المعنى من أهمّيّة في اختيار الحرف الدقيق عند ترجمته؛ وذلك من خلال إجراء مقارنة بين ترجمتين اثنتين لأهم ترجمات معاني القرآن الكريم المعتمدة إلى اللغة الإنجليزية، الأولى لمرمدوك بكتال، والثانية لمجمع خادم الحرمين الشريفين الملك فهد. وقد اعتمدت الدراسة في ذلك على المنهجين الاستقرائي والتحليلي؛ إذ بدأت الدراسة بتوضيح مفهوم حرف الجرّ، ثم انتقلت إلى مناقشة وتحليل الطرق والأساليب التي اتّبعتها كلّ ترجمة، وتوصلت الدراسة إلى أن إشكالية ترجمة حروف الجر تتلخص في عدم وجود مكافئات لغويّة ثابتة لها، فليس هناك آليّة ثابتة في استبدال حرف جرّ بآخر عند القيام بعمليّة الترجمة، فكل حرف من حروف الجرّ يكتسب دلالات معجميّة ونحويّة متنوعة يحدّدها السياق اللغويّ. الكلمات المفتاحية: حرف الجرّ، القرآن الكريم، الترجمة الإنجليزية، ترجمة بيكتال، ترجمة مجمع الملك فهد. Abstract This study aims to analyse English translations of the prepositions (ḥurūf jarr) in the holy Qur’an, and scrutinize the role of prepositions in delivering meanings. The implication of the meanings is determined based on choosing the exact preposition during the translation. Using inductive and analytical methods, this study conducts a comparative analysis between two major English translations of the Quran, one by Marmaduke Pickthall and the other by the King Fahd Complex. It looks into the methods and approaches adopted by both in dealing with the prepositions. This study finds out that the problem of translating Arabic preposition is the absence of precise equivalents in English. Since there is no definite mechanism for replacing one preposition with another during translation, each preposition requires various lexical and grammatical denotations determined by the linguistic context. Key words: Preposition (Íarf jarr), the Holy Qur’an, English Translation, Translation of Pickthall, Translation of King Fahd Complex.